Synergistic Impacts of Water Hyacinth Bloom and Organic Pollution on Water Quality and Public Health Risk - Sutrisno Anggoro; Nurjazuli Nurjazuli; Nine Elissa Maharani (JURNAL INFO KESEHATAN, 2026)
Multifunctional tropical reservoirs face increasing threats from water quality degradation due to anthropogenic activities, posing significant risks to both the ecosystem and public health. This study evaluates the synergistic impacts of water hyacinth (Eichhornia crassipes) bloom and organic pollution on Cengklik Reservoir. It assessed the combined effect of these factors on oxygen dynamics and inferred the potential risks to human health for communities reliant on the reservoir. The research utilized historical data (2020-2024) for Biochemical Oxygen Demand (BOD) and Dissolved Oxygen (DO) from the official BBWS Surakarta website. Standard test methods (SNI 6989.72.2009 for BOD and APHA 2017 for DO) were used to ensure data quality. This study indicates a synergistic interaction between organic pollution and water hyacinth proliferation that contributes to water quality degradation and conditions favorable for pathogen and toxin occurrence. A temporal trend analysis and a comparison with national water quality standards were performed. The analysis revealed a significant increase in average BOD concentrations (4.3-7.9 mg/L) and a decrease in average DO (3.78 mg/L) throughout the study period. These values exceeded the Class II water quality standard for BOD (3 mg/L) and did not comply with the DO standard (>4 mg/L) as per PP RI No. 22 of 2021. Linier regression= 0.820 (Not statistically significant. Simultaneously, BOD does not have a significant effect on DO. This indicates that the BOD variable is not an effective predictor of the DO variable). These findings indicate a high organic load and widespread oxygen depletion. This highlights the urgent need for an integrated management strategy to protect the reservoir’s ecological sustainability and the health of the surrounding community.